Water molds isolated from eggs and fry of striped catfish (Pangasianodon hypophthalmus) in the Mekong Delta of Viet Nam - Pham Minh Duc; Dang Thuy Mai Thy; Ngo Thi Mong Trinh; Tran Ngoc Tuan; Kishio Hatai (Insight Medical Publishing, 2015)
This study was carried out to isolate and identify fungal isolates causing fungal infected in the eggs and fries of stripped catfish in An Giang and Dong Thap Provinces. A total of 20 and 85 fungal isolates were isolated from infection fries and eggs samples of stripped catfish, respectively. All fungal isolates were identified as belonging to two genera Saprolegnia and Achlya. The optimal temperature for vegetative growth of four isolates Achlya sp. and Saprolegnia sp. was 30°C and 25°C, respectively. The vegetative growth of these isolates were able to tolerate up to 1% NaCl. The hatching rate of eggs challenge with fungus Achlya AG1213 at low and high dose were 48.7% and 34.0%, respectively. The hatching rate of eggs challenge with fungus Saprolegnia AG1219 at low and high dose were 55.3% and 32.0%, respectively. However, The hatching rate of eggs was 72.3% in the control group. This is the first report on fungi isolated from striped catfish eggs and fries at hatcheries in the Mekong Delta Vietnam.